Extended possibility of an active control of co-axially nested shear plasma formation due to electron cyclotron heatings. (19th September 2016) - Cho, T.; Hirata, M.
Abstract : Coaxially nested intense E× B sheared flow realized an upgraded stable mirror plasma regime. After such an external control of high vorticity formation due to electron cyclotron heating, significantly unstable plasmas appeared. Thereby, the associated cross-field transport caused a crash of plasmas. Its generalized physics and interpretation could prepare or extend to another possibility of stability in a field-reversed configuration (FRC), for instance. Such underlying physics bases of vorticity formation were essentially or partially performed in tokamaks and stellarators (solved problems). Nevertheless, it remains to be seen whether this mirror-based experimental evidence is applicable or not to open ended FRC devices. This open issue may give a solution of one of unsolved important problems, and possibly provide more generalized and externally controllable opportunities for not only FRC but wider plasma confinement improvements.